Performance evaluation of TiN coated CBN inserts during hard turning of AISI 4340 steel with using Taguchi-Grey-Fuzzy approach (International Journal of Emerging Trends in Science and Technology, 2017)
This Hard turning finds a broad range of applications in manufacturing industries. The high wear resistancealong with high dimensional accuracy is the primary attributes of the process. However, the critical setbackassociated with hard turning is the high heat generation at the cutting zone. It lead to earlier tool wear rateand causes the decrease in the machining performance. The cutting tool material plays a significant role indeciding the performance of hard turning. Therefore in this research work, an attempt has been made toinvestigate the performance of TiN coated CBN tools during machining of variable hardened AISI 4340steel. The cutting speed, feed rate, workpiece hardness and cutting tools (uncoated CBN and TiN coatedCBN) were selected as process parameters during experimentation. The cutting force, chip-tool interfacetemperature and material removal rate (MRR) was selected as performance parameters. The L-18 orthogonalarray from Taguchi approach was chosen to perform the experimental work. The grey relational techniquewas used to optimize the process parameters. The results from the grey relational model were verified byusing fuzzy logic. The experimental results indicate that tool material and feed rate are the significantprocess variables which influence the machining performance.